PENERAPAN AKUPRESURE SEBAGAI PENDEKATAN NON FARMAKOLOGIS UNTUK MENGURANGI NYERI KEPALA, NYERI PINGGANG DAN NYERI SENDI PADA MASYARAKAT DI DESA TUNGGUL PAWENANG - Triana, Iin; Dellia Dwi Kurnia; Elsa Amanda Tanesty; Ida Ayu Damayanti; Dwi Ilpa Ningsih; Nana Maulida; Dianah Kasso; Ega Dina Vianti; Reyhan Aprilio Pratama; Ridwan Agung Pratama (JOURNAL SAINS STUDENT RESEARCH, 2025)
Background : Acupressure is a safe and effective non-drug method for managing chronic pain. This study is designed to implement and evaluate the effectiveness of acupressure in reducing pain within rural communities. Approximately 70% of the residents of Tunggul Pawenang Village experience headaches, back pain, and joint pain, but a lack of knowledge (80% are unaware) about acupressure leads them to use risky over-the-counter medications. Methods : This community service activity involved 17 people in Tunggul Pawenang Village on November 5, 2025. The methods used were providing educational materials and demonstrating acupressure techniques, followed by an assessment of participants' knowledge. Results : The application of acupressure received a very positive response. The community showed enthusiasm, began using acupressure regularly, and found it helpful because the technique was easy to perform on their own and provided a significant relaxation effect that reduced pain intensity. Awareness of the risks of overuse of painkillers also increased, encouraging the preservation of safer acupressure therapy. Conclusion : Acupressure has proven to be an effective, safe, and sustainable solution for pain management in rural communities. This application successfully reduced pain intensity and improved the community's quality of life.